Application and evaluation of electrocoagulation techniques for the treatment of dyehouse effluents - Thole, Andile (Cape Peninsula University of Technology, 2015)
Thesis submitted in fulfillment of the requirements for the degree Master of Technology Chemical Engineering In the Faculty of Engineering at the Cape Peninsula University of Technology === Wet textile processing (WTP), is faced with many challenges that are related to operating costs and market competiveness. WTP uses large amounts of water and electricity, which constitute a big portion of operating costs of dyehouses and other costs are related to releasing large quantities of water, high concentrations of dyes and chemicals into the textile effluents with possible effluents discharge limits (EDL) penalty charges if EDL are exceeded. EDL penalty costs had become a normative part of the operating costs for some WTP textile factories, making the EDL penalties, a monthly cost item, because water utilities and the effluent discharge are not controlled and optimized. Cotton dyeing is a complicated chemi-physical-sorption process that is not easy to perform efficiently. Inefficient dyeing (off-shades and un-level dyeing) sometimes results in several reprocessing steps, leading to mega litres of water and chemical usage. Inefficient dyeing can also lead to higher concentrations of dyes and chemicals in the dyeing effluents. The main objectives of this study were to investigate the applicability of electrocoagulation (EC) in treatment of reactive dyes textile effluents for safe discharge into sewers or forreuse and also to evaluate EC reaction kinetics in removal of various pollutants from reactive dyes textile effluent with a batch electrocoagulation reactor (ECR). To achieve these objectives; textile effluents to be used had to be created instead of using factory effluents because textile effluents vary between dyeing batches and reaction kinetics study require constant and consistent composition of effluents. This was done by following the standard commercial sample cotton-dyeing procedures. The dyeing and pre-bleaching procedures were formulated from literature sources. The dyeing and pre-bleaching were done to create the reactive dyes textile effluents with commercial sample dyeing machines; Washtec-P and Pyrotec-MB2 at liquor ratios of 10:1 and 20:1.